2005
DOI: 10.1038/sj.cgt.7700814
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of hypoxia-induced BAX expression in a human glioblastoma xenograft model

Abstract: The effectiveness of radiation therapy for human brain tumors is limited by the presence of radiation-resistant hypoxic cells. In order to improve patient outcomes, therapeutic methods that increase hypoxic cell killing must be developed. To investigate the possibility of using the hypoxic tumor microenvironment itself as a target for gene therapy, we stably transfected U-251 MG human glioblastoma cells with constructs containing the suicide gene Bax under the regulation of a nine-copy concatemer of hypoxia re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
(21 reference statements)
1
21
0
1
Order By: Relevance
“…It has been reported that during hypoxia, the proapoptotic protein Bax is translocated from the cytosol to the mitochondria, resulting in cytochrome c release and caspase activation [52]. More recently, this has been confirmed by other observations that designate HIF-1 induction as the basis of Bax upregulation [53].…”
Section: Hypoxia and Apoptosissupporting
confidence: 70%
“…It has been reported that during hypoxia, the proapoptotic protein Bax is translocated from the cytosol to the mitochondria, resulting in cytochrome c release and caspase activation [52]. More recently, this has been confirmed by other observations that designate HIF-1 induction as the basis of Bax upregulation [53].…”
Section: Hypoxia and Apoptosissupporting
confidence: 70%
“…One of the main proapoptotic proteins is BAX protein of bcl-2 family (2). Many researchers have shown that over expression of BAX gene can overcome anti-apoptotic proteins and cause cancer cells' apoptosis (3,4,31,32). In this study it was shown that BAX over expression can lead to apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 72%
“…Tumor cells located in hypoxic tissue regions are resistant to both chemotherapy and radiotherapy and must be eradicated by alternative strategies [131]. Several genetic approaches have been validated in which HIF-1α-responsive promoters drive (i) production of toxic proteins or prodrug-converting enzymes such as the suicide genes bax [132], cytosine deaminase [133] or a Herpes simplex-derived thymidine kinase [134] or (ii) replication of oncolytic adenoviruses [135]. Gene delivery was accomplished either by conventional viral transduction (see below) or by anaerobic bacteria, which preferentially accumulate in hypoxic tumor tissues [136].…”
Section: Hypoxia-controlled Transgene Expressionmentioning
confidence: 99%